# x + 5 = (x over 2) - 6

x = ?

x + 5 = x/2 + 6

Double both sides of the equation.

2x + 10 = x + 12

Subract x+10 from both sides

x = 2

## To solve the equation x + 5 = (x/2) - 6, first let's simplify the right side by applying the distributive property. Distribute the (1/2) to both terms inside the parentheses:

x + 5 = (x/2) - 6

x + 5 = (1/2)x - 3

Next, we want to eliminate the fraction by multiplying every term by 2 to get rid of the denominator:

2(x + 5) = 2((1/2)x - 3)

2x + 10 = x - 6

Now, we can combine like terms on both sides of the equation:

2x - x = -6 - 10

x = -16

Thus, the value of x that satisfies the original equation is x = -16.